Magnesium Isoglycyrrhizinate Alleviates Alectinib-Induced Hepatotoxicity by Inhibiting Mitochondrial Damage-Mediated Pyroptosis - Chen Y; Wang C; Wu Y; Zeng Y; Xie S; Weng J; Guo L; Fu J; Zhou T; Zhang X; Zhou Z (Drug Design, Development and Therapy)
Yizhang Chen,1,2,* Chenxiang Wang,1,* Yuna Wu,3,* Yuhan Zeng,1,4 Shangjing Xie,5 Jialu Weng,5 Lei Guo,1,2 Jing Fu,1 Tao Zhou,1 Xiuhua Zhang,4 Ziye Zhou4,5 1Department of Pharmacy, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, People’s Republic of China; 2School of Pharmaceutical Sciences, Wenzhou Medical University, Wenzhou, Zhejiang, People’s Republic of China; 3The Eye Hospital, School of Ophthalmology & Optometry, Wenzhou Medical University, Wenzhou, People’s Republic of China; 4Clinical Research Center, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, People’s Republic of China; 5Zhejiang Key Laboratory of Intelligent Cancer Biomarker Discovery and Translation, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang People’s Republic of China*These authors contributed equally to this workCorrespondence: Ziye Zhou, Clinical Research Center and Zhejiang Key Laboratory of Intelligent Cancer Biomarker Discovery and Translation, The First Affiliated Hospital of Wenzhou Medical University, Nanbaixiang Street, Ouhai District, Wenzhou, 325000, People’s Republic of China, Tel +86-577-55579593, Email redd88@163.com Xiuhua Zhang, Clinical Research Center, The First Affiliated Hospital of Wenzhou Medical University, Nanbaixiang Street, Ouhai District, Wenzhou, 325000, People’s Republic of China, Tel +86-577-55579590, Email Wzzhangxiuhua@126.comIntroduction: Alectinib is a widely used first-line ALK inhibitor for fusion-positive non-small cell lung cancer. However, its clinical use is limited by hepatotoxicity, and its mechanism remains unclear. This study aims to elucidate how alectinib induces liver injury and to explore a potential protective strategy.Methods: In vitro, AML-12 hepatocytes were incubated with alectinib to determine cell viability and morphology by using CCK-8 assay and optical microscopy, respectively. Necrosis was assessed by flow cytometry after Annexin V-FITC/PI staining. Mitochondrial damage was analyzed by measuring membrane potential, ultrastructure, and respiratory chain complex activities using JC-1 staining under fluorescence microscopy, transmission electron microscopy, and assay kits, respectively. Intracellular reactive oxygen species (ROS) levels were detected using DCFH-DA staining and flow cytometry. Pyroptosis- and oxidative stress-related proteins (NLRP3, GSDMD-N, P20, cleaved IL-1β, Nrf2, HO-1) were quantified by Western blot. In vivo, C57BL/6J mice were divided into control, alectinib treatment, and alectinib plus magnesium isoglycyrrhizinate (MgIG) treatment groups. Serum ALT and AST were measured to assess liver function. Hepatic oxidative stress was evaluated by SOD and MDA levels. Inflammatory cytokines including IL-1β and TNF-α were measured by corresponding kits. Liver histopathology was examined by hematoxylin-eosin staining.Results: We found alectinib could induce the death of AML-12 hepatocytes. Alectinib impaired both the function and structure of mitochondria and caused a significant increase in ROS levels. The excessive accumulation of ROS triggered oxidative stress and finally resulted in cell pyroptosis in AML-12 cells. MgIG was found to alleviate mitochondrial damage and reduce ROS levels, restore the Nrf2/HO-1 signaling pathway, thereby inhibiting oxidative stress and pyroptosis caused by alectinib.Conclusion: Alectinib induces elevated ROS levels in hepatocytes by damaging mitochondria and causing oxidative stress in hepatocytes, which results in cell pyroptosis and ultimately hepatotoxicity, whereas MgIG can treat alectinib-induced hepatic injury by restoring mitochondrial function and structure.Keywords: alectinib, mitochondria damage, oxidative stress, pyroptosis, magnesium isoglycyrrhizinate